Construcción y destrucción en los Andes: terremotos, eventos geoclimáticos, calentamiento global y cambio climático - Bueno Mendoza, Alberto (2008)
The construction and architecture belong to the bigger inventions and the autonomous techniques’s achievements and the Antiguo Perú’s autogestionarias. the Andean People and such technical employees in the Colonia were like manpower in order to the Spaniards, and in the República, they faced up to the local construction, public and edifications prevailed, the massive urbanism and the vertical architecture. The earthquakes (tellurian phenomena permanent in our country and South America), they are destructive generating social, economic and sociopolitical complications. The events geoclimáticos and the climatic variation affect in the climatic extremes and oceanographic afectantes of life in the planet. the planet’s intelligent life has to reacting positively in favor of the healthy life and clean.